Synthesis, characterization, and organocatalytic application of chiral ionic liquids derived from (S, R)-noscapine. Issue 1 (2nd January 2018) - Kaur, Nirmaljeet; Chopra, Harish Kumar
ABSTRACT: ( S, R )-Noscapine, a phthalideisoquinoline alkaloid has been used as precursor for the synthesis of chiral ionic liquids (CILs). Noscapine based CILs have been synthesized from reaction between ( S, R )-noscapine and methyl iodide in acetonitrile at room temperature. The synthesized CILs have been characterized by 1 H NMR, 13 C NMR, EI-MS, and polarimetry techniques. These CILs have been used as organocatalysts in the enantioselective reduction of prochiral ketones to produce optically active secondary alcohols. The optically active secondary alcohols have been obtained with excellent yields and low to moderate enantiomeric excess (ee); also the complete enantiomeric excess (100% ee) has been achieved in some cases. GRAPHICAL ABSTRACT: